2017
DOI: 10.3102/0013189x17726282
|View full text |Cite
|
Sign up to set email alerts
|

Replicated Evidence of Racial and Ethnic Disparities in Disability Identification in U.S. Schools

Abstract: Federal legislation and policy increasingly seek to address minority overrepresentation in special education due to concerns that U.S. schools are misidentifying children as disabled based on their race or ethnicity. Yet whether and to what extent this is occurring is currently in dispute. We estimated racial disparities in disability identification using very large (e.g., Ns = 183,570, 165,540, and 48,560) student-level, nationally representative data sets and multivariate logistic regression including school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 54 publications
8
103
1
Order By: Relevance
“…Binet was adamant that his measure should not be used as a sole indicator of a child's intellectual potential and that intelligence can change and develop over the lifespan. His measure was the impetus for the Stanford-Binet, which, along with the Wechsler Intelligence Scale for Children, are the most commonly used IQ measures in the United States, where school children with disabilities are one of the most heavily tested populations [33]. The court cases covered in this article highlight the complicated relationship between intelligence and education vis a vis IDEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binet was adamant that his measure should not be used as a sole indicator of a child's intellectual potential and that intelligence can change and develop over the lifespan. His measure was the impetus for the Stanford-Binet, which, along with the Wechsler Intelligence Scale for Children, are the most commonly used IQ measures in the United States, where school children with disabilities are one of the most heavily tested populations [33]. The court cases covered in this article highlight the complicated relationship between intelligence and education vis a vis IDEA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, members of low-performing groups will have a higher likelihood of receiving lower scores, which, in turn, lead to an increased likelihood of ID diagnoses and decreased likelihood of LD diagnoses [31,32]. Morgan and colleagues [33,34] have found that minority children are underrepresented in special education classrooms compared to their White counterparts with similar profiles in academic achievement, income, and language status. Others, however, argue these data and analytical approaches do not adequately capture important factors and interdisciplinary nuances of IDEA and minority children with disabilities [35,36].…”
Section: Methodological Difficulties In Examining Intelligence and Ideamentioning
confidence: 99%
“…Academic achievement is a strong predictor of disability identification, and children from minority groups are more likely to experience academic difficulties at school entry (Hosp & Reschly, ; National Center for Education Statistics, ). After adjusting for individual levels of academic achievement and school level factors, African American children were 57% less likely to receive special education services compared to White children, and 53% less likely to be identified under specific learning disability compared to White children (Morgan et al, ). In our work, African American children in third grade had statistically significantly lower mean reading scores on the third grade end of grade test compared to White children ( p < .0001), perhaps explaining their increased likelihood of eligibility classification under specific learning disability.…”
Section: Discussionmentioning
confidence: 99%
“…A representation index is a form of the general relative risk calculation and is the ratio between any given group's representation in the identified gifted population and its representation in the overall student population. This is the approach most frequently used in education research, including studies of disproportionality in other areas of education, such as special education services (e.g., Morgan, Farkas, Hillemeier, & Maczuga, 2017) and school discipline (e.g., Gregory, Cornell, & Fan, 2011). For example, Peters et al (2019) found that African American and Latinx students were represented in identified gifted populations at approximately 57% and 70% of these students' prevalence in the overall K-12 student population.…”
Section: Quantifying Disproportionalitymentioning
confidence: 99%